EVALUATION OF POLYUNSATURATED FATTY ACIDS AND β-GLUCAN CONTAINING DIET ON GROWTH PERFORMANCE AND CONDITION FACTOR OF PABDAH CATFISH, OMPOK PABDA (HAMILTON, 1822) - Md. Sadam Hossain; Mohammad Moniruzzaman; Mohammad Matiur Rahman; Zakir Hossain (Indonesian Aquaculture Journal, 2022)
Nutritionally balanced diet and selection of appropriate species for culturing environment are important criteria in aquaculture. The present study was conducted to evaluate the effects of polyunsaturated fatty acids (PUFAs) and β-glucan containing diet (PBG) on growth performance, feed utilization, length-weight relationship, and condition factor of Pabdah catfish, Ompok pabda. In this study, squid extracted phospholipid and mushroom powder were used as the source of PUFAs and β-glucan, respectively, and formulated two isonitrogenous diets such as basal or control (CON) diet and PBG diet with maintaining 30% protein levels. During the study period, similar physicochemical conditions of water such as temperature, pH, and dissolved oxygen (DO) were 26.5 ± 2 °C, 7.4 ± 0.2, and 6.7 ± 0.5 ppm, respectively were maintained in each cistern. The results showed that final mean body weight, final mean length gain, food conversion ratio (FCR), specific growth rate (SGR), food conversion efficiency (%), hepato somatic index (HSI), kidney index (KI), and viscerosomatic index (VSI) were significantly (P<0.01 and P<0.05) higher in fish fed the PBG diet than that of fish fed the CON diet. The coefficient of determination showed a significant relationship (R2 = 0.956) between the length and weight of the treatment group. The length-weight relationship and relative condition factor (K) of Ompok pabda were significantly (P<0.05) affected by the PBG diet. The present study shows that the experimental diet more effective and achieves better growth performance, feed utilization, length-weight relationship, and condition factor of Ompok pabda.